Combination treatment of perifosine and valsartan showed more efficiency in protecting against pressure overload induced mouse heart failure - Wen-jing Li; Hai-han Liao; Hong Feng; Zi-ying Zhou; Shan-qi Mou; Nan Zhang; Hai-ming Wu; Hao Xia; Qi-zhu Tang (Elsevier, 2020)
The optimum strategy for heart failure (HF) treatment has yet to be elucidated. This study intended to test the benefit of a combination of valsartan (VAL) and perifosine (PER), a specific AKT inhibitor, in protecting against pressure overload induced mouse HF. Mouse were subjected to aortic banding (AB) surgery to establish HF models and then were given vehicle (HF), VAL (50 mg/kg/d), PER (30 mg/kg/d) or combination of VAL and PER for 4 weeks. Mouse with sham surgery treated with VEH were used for control (VEH). VAL or PER treatment could significantly alleviate mouse heart weight, attenuate cardiac fibrosis and improve cardiac function. The combination treatment of VAL and PER presented much better benefit compared with VAL or PER group respectively. PER treatment significantly inhibited AKT/GSK3β/mTORC1 signaling. Besides the classic AT1 inhibition, VAL treatment significantly inhibited MAPK (ERK1/2) signaling. Furthermore, VAL and PER treatment could markedly prevent neonatal rat cardiomyocyte hypertrophy and the activation of neonatal rat cardiac fibroblast. Combination of VAL and PER also presented superior beneficial effects than single treatment of VAL or PER in vitro experiments respectively. This study presented that the combination of valsartan and PER may be a potential treatment for HF prevention.